Relating faith and political action utopia in the theology of Gustavo Gutiérrez - Aguas, Raymond Bautista (ProQuest Dissertations & Theses Global, 2007)
"This dissertation investigates Gustavo Gutierrez's understanding of liberation as a three-dimensional process: (1) economic and political emancipation; (2) creation of a new humanity in a new society of justice; and (3) freedom from sin. The notion of "utopia" corresponds to the second dimension, and works as the bridge allowing for the relation of faith to political action without confusion or collapse. This dissertation argues that the notion of utopia serves as a central, unifying concept for Gutierrez's entire theological project. Chapter 1 examines the stages in the formation of Gutierrez's theology. First, Gutierrez studied in Europe where he was exposed to nouvelle theologie. Second, Gutierrez returned to Peru and its situation of injustice. Third, Gutierrez incorporated insights from the Second Vatican Council and Populorum Progressio. Fourth, Gutierrez's theology was confirmed at the Latin American bishops' conference held in Medellin, Colombia in 1968. Chapter 2 analyses utopia as treated in A Theology of Liberation : Gutierrez's sources for the notion, what he means by the notion, and how it operates throughout this work. This dissertation argues that utopia's essential role of mediating between faith and political action, allowing for relation without collapse, is necessary for properly interpreting Gutierrez's theology. Chapter 3 investigates how utopia functions throughout Gutierrez's subsequent works. Without explicitly treating of utopia, Gutierrez continues to structure his argument around utopia's mediating role as he discusses topics like spirituality, theology, and the Trinity. Chapter 4 investigates critics of Gutierrez: Cardinal Ratzinger, (Pope Benedict XVI), and "Radical Orthodoxy's" Daniel Bell. Ratzinger argues that Gutierrez's use of utopia results in a collapse of faith into politics. Bell argues that Gutierrez's theology keeps these poles mutually exclusive. This dissertation argues that a proper understanding of Gutierrez's use of utopia invalidates these criticisms. Chapter 5 examines the theology of the Philippines' Second Plenary Council. The council's appropriation of liberation theology's insights fail to adequately relate faith and political action because of a lack of understanding of utopia's mediating role within Gutierrez's three dimensions of liberation. This discussion of the council's theology confirms the importance of utopia as an essential concept in a theology of liberation."--Abstract.